Bleeding and thrombotic events occur early in children on durable ventricular assist devices. Issue 173 (January 2019) - Huang, Joanna Y.; Ignjatovic, Vera; Sheridan, Bennett J.; Mathew, Jacob; D'Udekem, Yves; Brink, Johann; Barton, Rebecca; Callea, Gabrielle; Morsman, Dominique; Donath, Susan; Opat, Stephen; Monagle, Paul
Abstract: Introduction: Durable Ventricular Assist Devices (VADs) are increasingly used in children with end-stage heart failure. Major complications are bleeding and thromboembolism (TE). Our objective was to determine the timing, incidence and risk factors for bleeding and TE in children implanted with VADs. Methods: This was a retrospective cohort of 8 years experience for children implanted with HeartWare HVAD and Berlin Heart EXCOR VADs at the Royal Children's Hospital, Melbourne. Results: 44 patients were implanted with Berlin Heart EXCOR or HeartWare HVAD devices. Major bleeding occurred in 17 patients (39%), 7 (16%) experienced thromboembolic strokes, 13 (30%) required device exchange for TE, and 4 (9%) experienced arterial thromboembolism. Twenty-seven patients (61%) were transplanted, three (7%) recovered, and six (14%) remain on device when censored. Eight patients (18%) died on VAD, with leading causes being thromboembolic stroke and intracranial bleeding. The majority of bleeding events and thromboembolic events occurred while patients were on unfractionated heparin (bleeding 66%, TE 40.5%) or transitioning between heparin and warfarin (bleeding 22%, TE 38%). Majority of patients were on more than one antiplatelet agent at the time of a major bleeding (87%) or thromboembolic (89%) event. Conclusions: The majority of bleeding and TE events occurring in children supported with durable VADs occur when they are on unfractionated heparin or transitioning to warfarin. Modifications to anticoagulation and monitoring in the early post-operative periods should be a research focus. Highlights: Bleeding and clotting risk is highest initially following pediatric VAD insertion. Another high-risk period is the transition between UFH and warfarin. Optimal strategies for anticoagulation are yet to be found during high-risk periods. Majority of thromboembolisms occurred despite patients being on antiplatelet therapy.